Composite material, positive electrode sheet and secondary battery
By using lithium iron silicate as the core, lithium iron phosphate as the shell layer, and a carbon layer in the middle as the positive electrode active material of the secondary battery, the problems of low SOC accuracy and cracking of composite particles of lithium iron phosphate batteries are solved, and the problem of low SOC accuracy and cracking of composite particles is achieved. The dual-platform characteristics of the battery charge and discharge curve and the improvement of SOC accuracy.
Patent Information
- Application Number
- CN202210009170.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-05
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-01-05
AI Technical Summary
The low SOC accuracy of lithium iron phosphate batteries makes it difficult for the battery management system to accurately estimate the residual power, and the volume changes of lithium iron silicate and lithium iron phosphate during charging and discharging, resulting in cracking of composite particles.
The composite material is prepared by spray granulation and calcination processes using lithium iron silicate as the core, lithium iron phosphate as the shell layer and a carbon layer in the middle.
The battery charge and discharge curve has dual platforms, which improves the BMS estimation SOC accuracy, and avoids the problem of composite particles cracking caused by inconsistent volume changes of lithium iron silicate and lithium iron phosphate.
Smart Images

Figure CN115832219B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a composite material, a positive electrode sheet, a secondary battery, a battery module, a battery pack, and an electrical device. Background Art
[0002] The depletion of energy resources has led to significant development in new energy storage devices. Secondary batteries have attracted considerable attention due to their high energy density, high capacity, excellent cycle stability, and environmentally friendly properties. Lithium iron phosphate (LiFePO4) cathode materials have become the mainstream cathode material due to their relatively low price, environmental friendliness, and high safety. The structure of LiFePO4 cathode materials dictates that during the charge and discharge process, a two-phase transition occurs from LiFePO4 to FePO4. This results in a long plateau in the discharge curve and a nonlinear relationship between the battery voltage and the remaining charge (State of Charge, SOC). This makes it difficult to estimate the remaining charge based on voltage, making it difficult for battery management systems to accurately measure the battery's SOC. Summary of the Invention
[0003] Currently, the mainstream method for improving the SOC accuracy of lithium iron phosphate batteries is to blend in other positive electrode materials to shorten the voltage platform. The selected positive electrode material needs to have a voltage range that is not much different from that of lithium iron phosphate, and it is best if the voltage and SOC have a linear relationship. Lithium iron silicate has the advantages of abundant raw material resources, low price, non-hygroscopicity, non-toxicity, environmental friendliness, and good thermal stability. It is also a hot research and development hotspot for secondary battery positive electrode materials. Among them, the operating voltage range of lithium iron silicate material is 2.0V to 3.7V, which is consistent with lithium iron phosphate, and the charging and discharging curve is very sloped, with a voltage platform of about 2.8V. The voltage platform of lithium iron phosphate material is about 3.2V. Mixing the two can form a dual platform, improving the accuracy of BMS estimation of SOC of lithium iron phosphate.
[0004] There are two main methods for mixing lithium iron phosphate with lithium iron silicate: physical mixing and composite structure construction. Physical mixing is to mix the two cathode materials in a certain proportion when preparing the cathode slurry. However, the electronic conductivity of the two is too different. The electronic conductivity of lithium iron phosphate is 10 -9 S / cm, lithium iron silicate is 10 -14 S / cm, resulting in large electrochemical polarization and concentration polarization during the charge and discharge process due to the large difference in electron transport capacity between the two. A composite structure combines the nanoparticles of the two into large particles, but in addition to the problem of excessive polarization, this process also suffers from inconsistent volume changes during charge and discharge. During charge and discharge, the volume of lithium iron phosphate changes little, while the volume of lithium iron silicate changes by more than 2%. This inconsistent volume expansion and contraction can cause cracking in the composite particles, exposing fresh interfaces that react with the electrolyte, ultimately leading to particle pulverization and failure.
[0005] In order to solve the above technical problems, the present application provides a composite material, which has lithium iron silicate as the core, lithium iron phosphate as the shell, and a carbon layer in the middle of the two. The composite material can be used as the positive electrode active material of the secondary battery, and its charge and discharge curve has a dual platform, which can solve the problem that the voltage platform of lithium iron phosphate is too long and the accuracy of BMS estimation of SOC is low. In particular, the composite material has lithium iron phosphate with high electronic conductivity as the shell to increase the interfacial electron transfer, and there is a carbon layer between the shell and the core. In addition to improving the electron conduction between lithium iron silicate and lithium iron phosphate, it also provides a buffer space for the volume expansion and contraction of lithium iron silicate, thereby solving the problem of cracking of composite particles caused by inconsistent volume expansion and contraction of lithium iron silicate and lithium iron phosphate.
[0006] In order to achieve the above-mentioned objectives, the present application provides a composite material and a preparation method thereof, and also provides a positive electrode sheet, a secondary battery, a battery module, a battery pack and an electrical device.
[0007] A first aspect of the present application provides a composite material, which is a spherical particle with a core-shell structure, wherein the core of the spherical particle comprises lithium iron silicate, the shell of the spherical particle comprises lithium iron phosphate, and a carbon layer is contained between the core and the shell.
[0008] In some embodiments, the spherical particles have a particle size represented by D50 of 3 μm to 15 μm.
[0009] In some embodiments, the lithium iron silicate and lithium iron phosphate are each particles having a single crystal structure.
[0010] In some embodiments, the particle size of the lithium iron silicate represented by D50 is 2 μm to 6 μm.
[0011] In some embodiments, the particle size of the lithium iron phosphate represented by D50 is 0.1 μm to 0.5 μm.
[0012] In some embodiments, the molar ratio of lithium iron phosphate to lithium iron silicate is 1:0.1 to 1:1.
[0013] A second aspect of the present application provides a method for preparing a composite material, comprising the following steps:
[0014] Step 1: mixing lithium iron silicate particles, silicone oil A and an organic solvent to obtain a mixture a, wherein the silicone oil A is a polysiloxane containing at least two silicon-hydrogen bonds;
[0015] Step 2: adding silicone oil B and a hydrosilylation catalyst to the mixture a of step 1 and mixing them to obtain a mixture b, wherein the silicone oil B is a polysiloxane containing at least two alkenyl groups;
[0016] Step 3: spray drying the mixture b from step 2 to form lithium iron silicate particles with a surface coated with an organic silicon layer;
[0017] Step 4: mixing lithium iron phosphate particles, a carbon source, water, and the lithium iron silicate particles coated with an organic silicon layer obtained in step 3, wherein the carbon source is an organic matter containing oxygen and / or nitrogen; and then forming secondary particles by spray granulation, wherein the secondary particles have a composite structure with the lithium iron silicate coated with the organic silicon layer as the core and the lithium iron phosphate coated with the carbon source as the shell;
[0018] Step 5: calcining the secondary particles obtained in step 4 under an inert atmosphere to obtain the composite material.
[0019] In some embodiments, the lithium iron silicate particles in step 1 have a single crystal structure.
[0020] In some embodiments, the particle size of the lithium iron silicate particles represented by D50 is 2 μm to 6 μm.
[0021] In some embodiments, the silicone oil A is methyl hydrogen silicone oil.
[0022] In some embodiments, the organic solvent is selected from one or more of dichloromethane, chloroform, toluene, xylene, and dichlorotoluene.
[0023] In some embodiments, the ratio of the volume of the organic solvent to the mass of the lithium iron silicate is 0.5 L / kg to 5 L / kg.
[0024] In some embodiments, the molar ratio of the lithium iron silicate particles to the silicone oil A is 1:0.01 to 1:0.15.
[0025] In some embodiments, the silicone oil B is vinyl silicone oil.
[0026] In some embodiments, the molar ratio of the silicone oil A to the silicone oil B is 1:1 to 1:4.
[0027] In some embodiments, the hydrosilylation catalyst in step 2 is selected from one or more of Karstedt catalyst, chloroplatinic acid, chlororhodic acid, and chloroiridic acid, more preferably Karstedt catalyst.
[0028] In some embodiments, the mass of the hydrosilylation catalyst is 0.001% to 0.05% of the total mass of the silicone oil A and the silicone oil B.
[0029] In some embodiments, step 3 is performed using a spray dryer, and the drying temperature of the spray dryer is 50°C to 200°C.
[0030] In some embodiments, the particles obtained in step 3 have a particle size of 2 μm to 6 μm, as represented by D50.
[0031] In some embodiments, the lithium iron phosphate particles in step 4 are single crystal structures.
[0032] In some embodiments, the particle size of the lithium iron phosphate particles represented by D50 is 0.1 μm to 0.5 μm.
[0033] In some embodiments, the carbon source of step 4 is selected from carbohydrates, polyethylene glycol, and polyacrylic acid.
[0034] In some embodiments, the molar ratio of the lithium iron phosphate particles in step 4 to the lithium iron silicate in step 1 is 1:0.1 to 1:1.
[0035] In some embodiments, the molar ratio of lithium iron phosphate to carbon source in step 4 is 1:0.01 to 1:0.1.
[0036] In some embodiments, step 4 is performed using a spray dryer, and the drying temperature of the spray dryer is 50°C to 200°C.
[0037] In some embodiments, the secondary particles obtained in step 4 have a particle size of 3 μm to 15 μm, as represented by D50.
[0038] In some embodiments, the inert atmosphere in step 5 is selected from nitrogen, argon, helium, and xenon.
[0039] In some embodiments, the calcination temperature is 300°C to 800°C.
[0040] In some embodiments, the calcination time is 2 hours to 10 hours.
[0041] In some embodiments, the composite material prepared by the method provided by the second aspect of this application is the composite material provided by the first aspect of this application.
[0042] A third aspect of the present application provides a positive electrode sheet comprising a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector; the positive electrode film layer comprises the composite material of the first aspect of the present application, or a composite material prepared by the method of the second aspect of the present application. Optionally, the positive electrode film layer further comprises a conductive agent and a binder.
[0043] The fourth aspect of the present application provides a secondary battery, comprising the composite material of the first aspect of the present application or the positive electrode sheet of the third aspect of the present application.
[0044] The fifth aspect of the present application provides a battery module, comprising the composite material of the first aspect of the present application, the positive electrode sheet of the third aspect of the present application, or the secondary battery of the fourth aspect of the present application.
[0045] The sixth aspect of the present application provides a battery pack, comprising the composite material of the first aspect of the present application, the positive electrode sheet of the third aspect of the present application, or the secondary battery of the fourth aspect of the present application, or the battery module of the fifth aspect of the present application.
[0046] The seventh aspect of the present application provides an electrical device, including the composite material of the first aspect of the present application, the positive electrode plate of the third aspect of the present application, or the secondary battery of the fourth aspect of the present application, or the battery module of the fifth aspect of the present application, or the battery pack of the sixth aspect of the present application.
[0047] The composite material provided in this application can be used as a positive electrode active material for a secondary battery to solve the problem of low accuracy in SOC estimation by a BMS. Furthermore, it also solves the problem of cracking of composite particles caused by inconsistent volume expansion and contraction of lithium iron silicate and lithium iron phosphate. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a SEM photograph of the composite material according to one embodiment of the present application.
[0049] Figure 2 for Figure 1 Magnified image of .
[0050] Figure 3 for Figure 2 Cross-sectional view of .
[0051] Figure 4 Schematic diagram of a secondary battery with a square structure according to one embodiment of the present application.
[0052] Figure 5 yes Figure 4 FIG. 1 is an exploded view of a secondary battery according to an embodiment of the present application.
[0053] Figure 6 Schematic diagram of a battery module according to one embodiment of the present application.
[0054] Figure 7 Schematic diagram of a battery pack according to one embodiment of the present application.
[0055] Figure 8 yes Figure 7 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0056] Figure 4-Figure 8Explanation of the reference numerals appearing in the figure: 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly.
[0057] Figure 9 Schematic diagram of a cylindrical secondary battery according to one embodiment of the present application.
[0058] Figure 10 yes Figure 9 The exploded view of the secondary battery of one embodiment of the present application is shown, and the figure marks are as follows: ① positive electrode top cover, ② positive electrode ear glue, ③ battery JR; ④ blue glue; ⑤ aluminum shell; ⑥ negative electrode ear glue; ⑦ negative electrode top cover.
[0059] Figure 11 FIG. 1 is a schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.
[0060] Figure 12 This is the particle size distribution curve of the positive electrode material prepared in Example 1.
[0061] Figure 13 1 is a charge and discharge curve diagram of Example 1 and Comparative Example 1.
[0062] Figure 14 The graph is a graph showing the battery capacity retention rate and cycle number corresponding to the positive electrode materials of Example 1 and Comparative Examples 1-2.
[0063] Figure 15 Graph showing battery rate performance corresponding to the positive electrode materials of Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0064] Below, the composite material and its preparation method, as well as the embodiments of the positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0065] The "ranges" disclosed herein are defined in terms of lower and upper limits, where a given range is defined by selecting a lower limit and an upper limit, and the selected lower and upper limits define the boundaries of the particular range. Ranges defined in this manner can be inclusive or exclusive of the end values and can be combined arbitrarily, i.e., any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60 to 120 and 80 to 110 are listed for a particular parameter, it is understood that ranges of 60 to 110 and 80 to 120 are also contemplated. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, the following ranges are all contemplated: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4, and 2 to 5. In this application, unless otherwise indicated, the numerical range "a to b" is a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0066] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0067] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0068] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0069] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0070] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0071] [Composite materials and preparation methods]
[0072] In one embodiment of the present application, a composite material is proposed, which is a spherical particle with a core-shell structure, wherein the core of the spherical particle comprises lithium iron silicate, the shell of the spherical particle comprises lithium iron phosphate, and carbon is contained between the core and the shell. The composite material provided by the present application has lithium iron silicate as the core, lithium iron phosphate as the shell, and a carbon layer in the middle. The operating voltage range of lithium iron silicate and lithium iron phosphate is close, which is 2.0V to 3.7V, while the voltage platform of lithium iron silicate is about 2.8V and that of lithium iron phosphate is about 3.2V. When the composite material is used as the positive active material of a secondary battery, the charge and discharge curve of the battery can have a dual platform, which can solve the problem that the voltage platform of lithium iron phosphate is too long and the accuracy of BMS estimation of SOC is low.
[0073] Furthermore, the composite material provided by the present application is lithium iron phosphate (10 -9 S / cm) as the shell, lithium iron silicate with low electronic conductivity (10 -14 S / cm) as the core, which can increase interfacial electron transport. At the same time, the carbon layer between the core and shell can improve electron conduction between lithium iron silicate and lithium iron phosphate, and provide a buffer space for the volume expansion and contraction of lithium iron silicate.
[0074] The inventors have found that when the particle size of the spherical particles, represented by D50, is between 3 μm and 15 μm, the composite material can have a suitable compaction density and specific surface area, and the particles are not easily cracked, thus avoiding the deterioration of the power performance of the battery during use. Therefore, in some embodiments, the particle size of the spherical particles, represented by D50, is between 3 μm and 15 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm.
[0075] In some embodiments, the lithium iron silicate and lithium iron phosphate are each particles having a single crystal structure. Lithium iron silicate particles with a larger particle size can be selected to facilitate the formation of a core-shell structure. In some embodiments, the particle size of the lithium iron silicate particles represented by D50 is 2μm to 6μm, for example, 2μm, 3μm, 4μm, 5μm or 6μm. In some embodiments, the particle size of the lithium iron phosphate represented by D50 is 0.1μm to 0.5μm, for example, 0.1μm, 0.2μm, 0.3m, 0.4μm or 0.5μm. The shell layer may include multiple lithium iron phosphate particles. Lithium iron phosphate particles with a particle size of 0.1μm to 0.5μm can be evenly coated on the surface of the lithium iron silicate to better form a coating layer.
[0076] The composite structure of the present invention contains carbon, which can be distributed continuously or discontinuously on the surface of the lithium iron silicate core, forming a continuous or discontinuous carbon layer. In some embodiments, the carbon layer between the core and the shell is formed by coating the lithium iron silicate with organosilicon. Therefore, in addition to carbon, the space between the core and the shell may also contain silicon dioxide generated during the formation of the carbon layer.
[0077] The carbon layer content can be selected appropriately based on actual needs, thereby maximizing the carbon layer's ability to enhance electron conduction while minimizing the negative impact on the energy density of the positive electrode material due to excessive carbon layer content. In some embodiments, the mass ratio of lithium iron silicate to carbon layer is 100:3 to 100:12, for example, 100:3 to 100:4, 100:4 to 100:6, 100:6 to 100:8, 100:8 to 100:10, 100:10 to 100:12, for example, 100:11.25.
[0078] Furthermore, the lithium iron phosphate constituting the shell layer can also be coated with carbon. The carbon coating the lithium iron phosphate can also play a role in improving electron conduction and buffering the volume change of lithium iron silicate. The specific capacity of lithium iron silicate in the operating voltage range of lithium iron phosphate is low, so the amount added should not be too much, and it can play the role of adjusting the voltage platform. In some embodiments, the molar ratio of lithium iron phosphate to lithium iron silicate is 1:0.1 to 1:1, for example 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1. Figures 1 to 3 The morphology of the composite material provided by the present application is shown as an example. As can be seen from the figure, the composite material provided by the present application is a secondary particle, which has a high sphericity. The particle enlargement diagram ( Figure 2 ) shows that the primary lithium iron phosphate particles are evenly distributed on the surface of the secondary particles. From the cross-sectional view ( Figure 3 ) It can be seen that the core of the secondary particle is a large single crystal of lithium iron silicate, the middle is a dot-shaped carbon layer, and the outer layer is a lithium iron phosphate layer.
[0079] In one embodiment of the present application, a method for preparing a composite material is proposed, comprising the following steps:
[0080] Step 1: mixing lithium iron silicate particles, silicone oil A and an organic solvent to obtain a mixture a, wherein the silicone oil A is a polysiloxane containing at least two silicon-hydrogen bonds;
[0081] Step 2: adding silicone oil B and a hydrosilylation catalyst to the mixture a of step 1 and mixing them to obtain a mixture b, wherein the silicone oil B is a polysiloxane containing at least two alkenyl groups;
[0082] Step 3: spray drying the mixture b from step 2 to form lithium iron silicate particles with a surface coated with an organic silicon layer;
[0083] Step 4: mixing lithium iron phosphate particles, a carbon source, water, and the lithium iron silicate particles coated with an organic silicon layer obtained in step 3, wherein the carbon source is an organic matter containing oxygen and / or nitrogen; and then forming secondary particles by spray granulation, wherein the secondary particles have a composite structure with the lithium iron silicate coated with the organic silicon layer as the core and the lithium iron phosphate coated with the carbon source as the shell;
[0084] Step 5: calcining the secondary particles obtained in step 4 under an inert atmosphere to obtain the composite material.
[0085] In the method for preparing a composite material provided by the present application, secondary particles with organosilicon-coated lithium iron silicate as the core and carbon-source-coated lithium iron phosphate as the shell are formed by spray granulation, and then calcined to obtain a spherical particle composite material with a core-shell structure. The composite material uses lithium iron phosphate with high electronic conductivity as the shell to increase interfacial electron transport. There is a carbon layer between the shell and the core, which not only improves the electronic conduction between lithium iron silicate and lithium iron phosphate, but also provides a buffer space for the volume expansion and contraction of lithium iron silicate. Organosilicon is calcined in an inert atmosphere to obtain silicon dioxide and carbon, which will slightly reduce the capacity of the positive electrode material, but will greatly improve the electronic conductivity and cycle performance.
[0086] The method of the present invention includes the step of coating lithium iron silicate particles with organosilicon. A polysiloxane containing at least two silicon-hydrogen bonds (silicone oil A) and a polysiloxane containing at least two alkenyl groups (silicone oil B) are coated on the surface of the lithium iron silicate particles. The particles are cured under heating and catalytic conditions, and then calcined to form a compact, non-detachable carbon layer.
[0087] In some embodiments, step 1 can use lithium iron silicate particles with a single crystal structure as a raw material. In some embodiments, the particle size of the lithium iron silicate particles represented by D50 is 2μm to 6μm (for example, 2μm, 3μm, 4μm, 5μm or 6μm). Selecting large particles of lithium iron silicate facilitates surface coating with lithium iron phosphate to form a lithium iron phosphate coating layer, thereby avoiding the formation of a mixed structure rather than a core-shell structure due to the particles being too small. Silicone oil A can be selected from polysiloxanes containing at least two (for example, 2, 3, 4 or more) silicon-hydrogen bonds, such as methyl hydrogen silicone oil often used in hydrosilylation reactions.
[0088] In step 1, an organic solvent that can dissolve the polysiloxane and does not react with the lithium iron silicate and lithium iron phosphate can be selected. A suitable organic solvent can improve the dispersion of the catalyst in the polysiloxane and also enhance the fluidity of the lithium iron silicate and lithium iron phosphate. Useful organic solvents include, but are not limited to, one or more of dichloromethane, chloroform, toluene, xylene, and dichlorotoluene.
[0089] In some embodiments, the ratio of the volume of the organic solvent to the mass of the lithium iron silicate is 0.5 L / kg to 5 L / kg (e.g., 0.5 L / kg to 1 L / kg, 1 L / kg to 2 L / kg, 2 L / kg to 3 L / kg, 3 L / kg to 4 L / kg, or 4 L / kg to 5 L / kg). Within this range, the lithium iron silicate and lithium iron phosphate can be ensured to have good fluidity while avoiding excessive solvent that may make drying difficult in subsequent processes. In some embodiments, silicone oil B is vinyl silicone oil.
[0090] The ratio of silicone oil A to silicone oil B can be adjusted according to actual needs to achieve a suitable degree of curing. In some embodiments, the molar ratio of silicone oil A to silicone oil B is 1:1 to 1:4 (e.g., 1:1, 1:2, 1:3 or 1:4).
[0091] Commonly used hydrosilylation catalysts can be used, such as one or more of Karstedt catalyst, chloroplatinic acid, chlororhodic acid, and chloroiridic acid, preferably Karstedt catalyst, which is more commonly used and has higher activity. The catalyst that plays an active role is platinum, and a platinum concentration of about 10ppm can play a curing role. The higher the concentration, the faster the curing time, but too high a concentration may cause platinum deposition to form platinum black. Therefore, the amount of the catalyst used can be selected according to actual needs. In some embodiments, the mass of the hydrosilylation catalyst is 0.001% to 0.05% of the total mass of the silicone oil A and the silicone oil B, for example, 0.001% to 0.005%, 0.005% to 0.01% or 0.01% to 0.05%.
[0092] The ratio of lithium iron silicate particles to silicone oil can be adjusted as needed to form an appropriate carbon layer content, thereby ensuring that the carbon layer enhances electron conduction without compromising the energy density of the positive electrode material due to excessive carbon layer content. In some embodiments, the molar ratio of the lithium iron silicate particles to the silicone oil A is 1:0.01 to 1:0.15, for example, 1:0.01 to 1:0.05, 1:0.05 to 1:0.1, or 1:0.1 to 1:0.15.
[0093] In some embodiments, step 2 comprises: adding lithium iron silicate, an organic solvent, and silicone oil A to a blender and mixing them uniformly to obtain a mixture A; mixing silicone oil B and a catalyst to obtain a mixture B; and then uniformly mixing mixtures A and B. In some embodiments, mixture B can be added to mixture A while stirring, and after uniform mixing, mixture C is obtained.
[0094] A spray dryer can be used to form lithium iron silicate particles coated with an organosilicon layer. During this process, silicone oil A and silicone oil B undergo a hydrosilylation reaction under the action of a catalyst. The hydrosilylation reaction, also known as thermal curing, occurs rapidly under heating conditions and essentially does not occur at room temperature. Through the hydrosilylation reaction, a dense, non-detachable carbon layer can be formed on the surface of the lithium iron silicate. The hydrosilylation reaction can be initiated at approximately 50°C, and the organosilicon cures rapidly. The upper limit of the curing temperature generally does not exceed 200°C to avoid excessive temperatures that increase the brittleness of the organosilicon and to avoid excessive energy consumption. Therefore, in some embodiments, the drying temperature of the spray dryer is 50-200°C, for example, 50-70°C, 70-100°C, 100-130°C, 130-150°C, 150-170°C, or 170-200°C. In some embodiments, the lithium iron silicate particles with a surface-coated organic silicon layer obtained in step 3 have a particle size represented by D50 of 2 μm to 6 μm (eg, 2 μm, 3 μm, 4 μm, 5 μm, or 6 μm).
[0095] Afterwards, the organosilicon-coated lithium iron silicate particles obtained in step 3, the lithium iron phosphate particles, the carbon source and water are added into a stirrer and mixed evenly, and then transferred into a spray dryer for spray granulation.
[0096] In some embodiments, the lithium iron phosphate particles have a single crystal structure. Lithium iron phosphate particles with a relatively small particle size can be selected to facilitate uniform coating of the lithium iron phosphate on the surface of the lithium iron silicate, making it easier to form a coating layer. In some embodiments, the lithium iron phosphate particles have a particle size (D50) of 0.1 μm to 0.5 μm (e.g., 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, or 0.5 μm).
[0097] Suitable nitrogen- and / or oxygen-containing small or large organic molecules can be selected as the carbon source for coating the lithium iron phosphate particles. These can be naturally occurring or synthetic, including but not limited to carbohydrates, polyethylene glycol, polyacrylic acid, etc. Carbohydrates can be monosaccharides, oligosaccharides, or polysaccharides, such as glucose, sucrose, or starch. Glucose, starch, and sucrose are preferred carbon sources because they are raw materials for synthesizing lithium iron phosphate.
[0098] An appropriate amount of water may be added as needed to dissolve the carbon source and improve the fluidity of the material. Deionized water may be used to minimize the introduction of impurities. In some embodiments, the amount of water added is 0.5 L / kg to 5 L / kg (e.g., 0.5 L / kg to 1 L / kg, 1 L / kg to 2 L / kg, 2 L / kg to 3 L / kg, 3 L / kg to 4 L / kg, or 4 L / kg to 5 L / kg) based on the total mass of lithium iron silicate and lithium iron phosphate.
[0099] In some embodiments, the molar ratio of the lithium iron phosphate particles added in step 4 to the lithium iron silicate in step 1 is 1:0.1 to 1:1 (e.g., 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, or 1:1). Lithium iron silicate has a low specific capacity within the operating voltage range of lithium iron phosphate, so the amount added should not be too large; it is sufficient to regulate the voltage platform.
[0100] The ratio of lithium iron phosphate to carbon source can be adjusted according to actual needs to form a carbon coating layer with an appropriate content, so that the carbon layer can play the role of improving electron conduction without affecting the energy density of the positive electrode material due to excessive carbon content. In some embodiments, the molar ratio of lithium iron phosphate to carbon source added in step 4 is 1:0.01 to 1:0.1, for example, 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09 or 1:0.1.
[0101] Organosilicon-coated lithium iron silicate particles, lithium iron phosphate particles, and a carbon source are spray-granulated to form secondary particles. Spray granulation can be performed using a spray dryer, and the accessories used may be different from those used for spray drying. In some embodiments, the drying temperature of the spray dryer is 50°C to 200°C, for example, 50°C to 70°C, 70°C to 100°C, 100°C to 130°C, 130°C to 150°C, 150°C to 170°C, or 170°C to 200°C. Within this temperature range, the organosilicon further solidifies, and at the same time, the solvent can be fully evaporated.
[0102] In the present invention, the lithium iron silicate particles and the lithium iron phosphate particles are referred to as primary particles, and the particles formed by spray granulation are referred to as secondary particles. The secondary particles are composed of a plurality of primary particles. In some embodiments, the secondary particles obtained in step 4 have a particle size, as represented by D50, of 3 μm to 15 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm.
[0103] Since the coating formed by spray granulation is not firmly bonded, the intermolecular force is enhanced by calcining so that the coating does not fall off. The secondary particles obtained in step 4 are calcined under an inert atmosphere, and the inert atmosphere can be selected from nitrogen, argon, helium, and xenon. The upper limit of the calcination temperature can be set near the synthesis temperature of lithium iron phosphate to avoid excessively high temperatures that may cause the material to melt and form large single crystals, resulting in deterioration of dynamic properties. Therefore, in some embodiments, the calcination temperature is 300°C to 800°C (e.g., 300°C to 400°C, 400°C to 500°C, 500°C to 600°C, 600°C to 700°C, or 700°C to 800°C). In some embodiments, the calcination time is 2h to 10h (e.g., 2h to 4h, 4h to 6h, 6h to 8h, or 8h to 10h).
[0104] In the method of the present invention, the spray drying temperature and the calcination temperature are both lower than or close to the synthesis temperature of lithium iron phosphate and lithium iron silicate, and thus have little effect on the single crystal structure and particle size of lithium iron phosphate and lithium iron silicate. In addition, there is essentially no loss of lithium iron phosphate and lithium iron silicate during the treatment process, so the molar ratio of the two in the composite material relative to the molar ratio of the raw materials does not change substantially. In some embodiments, the composite material obtained by the method provided in the second aspect of the present application is the composite material provided in the first aspect of the present application.
[0105] [Positive electrode sheet and preparation method]
[0106] A third aspect of the present application provides a positive electrode sheet comprising a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector; the positive electrode film layer comprises the composite material of the first aspect of the present application, or a composite material prepared by the method of the second aspect of the present application. Optionally, the positive electrode film layer further comprises a conductive agent and a binder.
[0107] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0108] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0109] In the positive electrode film layer, the composite material of the first aspect of the present application, or the composite material prepared by the method of the second aspect of the present application is used as the positive electrode active material.
[0110] In some embodiments, the positive electrode film layer may further include other traditional materials that can be used as positive electrode active materials for batteries. These positive electrode active materials can be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds, etc. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, one or more of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0111] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorinated acrylate resin. In some embodiments, the binder is PVDF.
[0112] In some embodiments, the positive electrode film layer may further optionally include a conductive agent. As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the conductive agent is carbon black (e.g., conductive carbon black SP).
[0113] In some embodiments, the positive electrode film layer comprises the composite material of the first aspect of the present application, or comprises the composite material prepared by the method of the second aspect of the present application; the positive electrode film layer further comprises a conductive agent and a binder.
[0114] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after cold pressing, slitting and other processes, the positive electrode sheet is obtained.
[0115] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.
[0116] [Secondary battery]
[0117] In one embodiment of the present application, a secondary battery is provided.
[0118] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.
[0119] [Negative electrode]
[0120] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0121] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0122] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0123] In some embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As an example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, etc. The silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from one or more of elemental tin, tin oxide compounds and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0124] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0125] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0126] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0127] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after cold pressing, slitting and other processes, the negative electrode sheet can be obtained.
[0128] [Electrolytes]
[0129] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0130] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.
[0131] In some embodiments, the electrolyte salt may be selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0132] In some embodiments, the solvent may be selected from one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0133] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0134] [Isolation film]
[0135] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0136] In some embodiments, the material of the separator can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0137] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0138] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0139] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0140] The present application has no particular restrictions on the shape of the secondary battery, which can be cylindrical, square or any other shape. For example, Figure 4 The secondary battery 5 is a square structure as an example.
[0141] In some embodiments, reference Figure 5 , the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0142] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0143] Figure 6 4 is an example of a battery module. Figure 6 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length of the battery module 4. Of course, they may also be arranged in any other manner. The plurality of secondary batteries 5 may further be fixed by fasteners.
[0144] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0145] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0146] Figure 7 and Figure 8 The battery pack 1 is used as an example. Figure 7 and Figure 8 The battery pack 1 may include a battery box and multiple battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner in the battery box.
[0147] Figure 9 is a secondary battery with a cylindrical structure as an example. In some embodiments, referring to Figure 10 The cylindrical secondary battery includes: ① positive electrode top cover, ② positive electrode ear glue, ③ battery JR; ④ blue glue; ⑤ aluminum shell; ⑥ negative electrode ear glue; ⑦ negative electrode top cover.
[0148] In addition, the present application also provides an electric device, which includes one or more of the secondary batteries, battery modules, or battery packs provided in the present application. The secondary batteries, battery modules, or battery packs can be used as the power source of the electric device, and can also be used as the energy storage unit of the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.
[0149] As the electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0150] Figure 11 This is an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0151] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0152] Example
[0153] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0154]
Preparation of positive electrode materials
[0155] Example 1 Preparation of composite materials
[0156] 1. Add 10 mol of lithium iron silicate, 1 L of dichloromethane, and 0.015 mol of methyl hydrogen silicone oil into a blender and mix well to obtain mixture A.
[0157] 2. 0.015 mol of vinyl silicone oil and Karstedt catalyst were mixed evenly, wherein the amount of the catalyst was 0.005% of the total mass of the methyl hydrogen silicone oil and the vinyl silicone oil, to obtain a mixture B.
[0158] 3. Add mixture B to mixture A while stirring, mix well to obtain mixture C, transfer mixture C to a spray dryer, and spray dry at 100°C to obtain dry organosilicon-coated lithium iron silicate secondary particles with a particle size D50 of 4 μm.
[0159] 4. The organosilicon-coated lithium iron silicate secondary particles obtained in step 3 were mixed evenly with 30 mol of lithium iron phosphate particles, 1.5 mol of glucose, and 10 L of deionized water to obtain a mixture D, which was transferred to a spray dryer and spray granulated at 100°C to obtain dry lithium iron phosphate-coated lithium iron silicate positive electrode material secondary particles with a particle size D50 of 10 μm.
[0160] 5. The composite cathode material obtained in step 4 was calcined at 400°C in a nitrogen atmosphere for 4 hours to obtain a composite structure with lithium iron silicate as the core, lithium iron phosphate as the shell, and a carbon layer in between.
[0161] Example 2
[0162] Except that the amount of methyl hydrogen silicone oil was changed to 0.0075 mol, the other steps of Example 2 were the same as those of Example 1.
[0163] Example 3
[0164] Except that the amount of vinyl silicone oil was changed to 0.03 mol, the other steps of Example 3 were the same as those of Example 1.
[0165] Example 4
[0166] Except that the calcination temperature is changed to 600° C., the other steps of Example 4 are the same as those of Example 1.
[0167] Example 5
[0168] Except that the calcination time is changed to 2 h, the other steps of Example 5 are the same as those of Example 1.
[0169] Example 6
[0170] Except that the amount of lithium iron phosphate was changed to 20 mol, the other steps of Example 6 were the same as those of Example 1.
[0171] Example 7
[0172] Except that the amount of glucose was changed to 0.6 mol, the other steps of Example 7 were the same as those of Example 1.
[0173] Comparative Example 1
[0174] Lithium iron phosphate is used as the positive electrode material.
[0175] Comparative Example 2
[0176] 1. Mix 10 mol of lithium iron silicate particles, 30 mol of lithium iron phosphate particles, 1.5 mol of glucose, and 10 L of deionized water. Transfer the resulting mixture to a spray dryer and spray granulate at 100°C to obtain dry lithium iron phosphate and lithium iron silicate mixed secondary particles with a particle size D50 of 2 μm.
[0177] 2. The secondary particles obtained in the second step were calcined at 400°C in a nitrogen atmosphere for 4 h to obtain a composite structure of carbon / lithium iron phosphate / lithium iron silicate.
[0178]
Preparation of positive electrode sheet
[0179] The positive electrode material obtained in the embodiment or comparative example, the conductive agent carbon black, the binder polyvinylidene fluoride (PVDF), and the solvent N-methylpyrrolidone (NMP) are fully stirred and mixed in a weight ratio of 67.34:30:28.86:2.7:1.1 to obtain a positive electrode slurry; the positive electrode slurry is then evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain a positive electrode sheet.
[0180]
Preparation of negative electrode sheet
[0181] The active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are dissolved in the solvent deionized water in a weight ratio of 96.2:0.8:0.8:1.2, and mixed evenly to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil once or multiple times, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.
[0182] Preparation of electrolyte
[0183] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed uniformly in a volume ratio of 3 / 7, 12.5% LiPF6 lithium salt was added and dissolved in the organic solvent, and stirred uniformly to obtain an electrolyte.
[0184]
Isolation film
[0185] Polypropylene film is used as the isolation film.
[0186]
Preparation of secondary batteries
[0187] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator between the positive and negative sheets acting as an insulator. The cells are then wound to form a bare cell. The tabs are then welded to the bare cell and placed in an aluminum shell. The cells are then baked at 100°C to remove moisture. The electrolyte is then injected and sealed to create an uncharged battery. The uncharged battery then undergoes a series of processes, including resting, hot and cold pressing, formation, shaping, and capacity testing, to produce a lithium-ion battery product.
[0188]
Test of parameters related to positive electrode active materials
[0189] 1. Volume average particle size D50 test
[0190] Equipment model: Malvern 2000 (MasterSizer 2000) laser particle size analyzer, reference standard process: GB / T19077-2016 / ISO 13320:2009, specific test process: Take an appropriate amount of sample to be tested (the sample concentration is 8% to 12% obscuration), add 20ml of deionized water, and simultaneously ultraviolet (53kHz / 120W) for 5 minutes to ensure that the sample is completely dispersed. Then, the sample is measured according to GB / T19077-2016 / ISO 13320:2009 standard.
[0191] Figure 12 3 is a particle size distribution curve of the positive electrode material prepared in Example 1. As can be seen from the figure, the D50 of the positive electrode material is 10 μm, and the particle size is uniform.
[0192] 2. Morphology test
[0193] The morphology of the samples was observed using a ZEISS Sigma 300 scanning electron microscope according to the standard JY / T010-1996.
[0194] Figure 1-Figure 3 The SEM photo of the secondary particles of the positive electrode material obtained in Example 1 is shown in FIG. Figure 1It can be seen that the secondary particles have high sphericity, and the particle enlargement diagram ( Figure 2 ) shows that the primary lithium iron phosphate particles are evenly distributed on the surface of the secondary particles. From the cross-sectional view ( Figure 3 ) It can be seen that the core of the secondary particle is a large single crystal of lithium iron silicate, the middle is a dot-shaped carbon layer, and the outer layer is a lithium iron phosphate layer.
[0195]
Battery performance test
[0196] 1. Battery charge and discharge test
[0197] Taking Example 1 as an example, the battery charge and discharge test process is as follows: at 25°C, the battery corresponding to Example 1 is charged at a constant current of 1 / 3C to 3.7V, then charged at a constant voltage of 3.7V to a current of 0.05C, left for 5 minutes, and then discharged at 1 / 3C to 2.0V to obtain a charge and discharge curve graph.
[0198] Figure 13 The charge and discharge curves of Example 1 and Comparative Example 1 are shown. As can be seen from the figure, compared with the long platform of lithium iron phosphate, the composite material prepared in Example 1 has a double platform, which is convenient for improving the accuracy of BMS in estimating the remaining power by identifying the voltage.
[0199] 2. Battery capacity retention test
[0200] Taking Example 1 as an example, the battery capacity retention rate test process is as follows: At 25°C, the corresponding battery of Example 1 is charged at a constant current of 1 / 3C to 3.7V, then charged at a constant voltage of 3.7V to a current of 0.05C, left for 5 minutes, and then discharged at 1 / 3C to 2.0V. The resulting capacity is recorded as the initial capacity C0. The above steps are repeated for the same battery, and the battery discharge capacity Cn after the nth cycle is recorded. The battery capacity retention rate after each cycle is Pn = Cn / C0 × 100%. The 200 points P1, P2...P200 are used as the vertical axis and the corresponding number of cycles is used as the horizontal axis to obtain a curve chart of battery capacity retention rate and cycle number.
[0201] Figure 14 The following is a graph showing the capacity retention and cycle number of the batteries corresponding to the positive electrode materials of Example 1 and Comparative Examples 1-2. As can be seen from the graph, the battery corresponding to the positive electrode material of Example 1 has similar cycle capacity as the battery using lithium iron phosphate as positive electrode material 1. However, the performance of the battery corresponding to the positive electrode material prepared in Comparative Example 2 deteriorates compared to Example 1 and Comparative Example 1 due to the large polarization between lithium iron phosphate and lithium iron silicate.
[0202] 3. Battery rate performance test
[0203] Taking Example 1 as an example, the battery rate performance test process is as follows: At 25°C, the corresponding battery of Example 1 is charged at a constant current of 1 / 3C to 3.7V, then charged at a constant voltage of 3.7V to a current of 0.05C, left for 5 minutes, and then discharged at 0.2C to 2.0V. This charge and discharge is repeated 5 times, and the resulting capacities are recorded as C1-C5. The capacities C6-C30 are then obtained by discharging at rates of 0.5C, 1C, 2C, 3C, and 0.2C, respectively. The battery rate performance graph is obtained with the 30 points C1-C30 as the vertical axis and the corresponding number of cycles as the horizontal axis.
[0204] Figure 15 Figure 2 shows the rate performance of the batteries corresponding to the positive electrode materials of Example 1 and Comparative Examples 1-2. As can be seen from the figure, the battery corresponding to the positive electrode material of Example 1 has similar rate performance to that of the battery using lithium iron phosphate as the positive electrode material. However, the performance of the battery corresponding to the positive electrode material prepared in Comparative Example 2 is worse than that of Example 1 and Comparative Example 1 due to the large polarization between lithium iron phosphate and lithium iron silicate.
[0205] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A composite material, which is a spherical particle with a core-shell structure, wherein the core of the spherical particle comprises lithium iron silicate, the shell layer of the spherical particle comprises lithium iron phosphate, and a carbon layer is comprised between the core and the shell layer. 2 . The composite material according to claim 1 , wherein the particle size of the spherical particles represented by D50 is 3 μm to 15 μm. 3 . The composite material according to claim 1 , wherein the lithium iron silicate and the lithium iron phosphate are particles each having a single crystal structure. 4 . The composite material according to claim 1 , wherein the particle size of the lithium iron silicate represented by D50 is 2 μm to 6 μm. 5 . The composite material according to claim 1 , wherein the particle size of the lithium iron phosphate represented by D50 is 0.1 μm to 0.5 μm. 6 . The composite material according to claim 1 , wherein the molar ratio of lithium iron phosphate to lithium iron silicate is 1:0.1 to 1:
1.
7. A method for preparing a composite material, comprising the following steps: Step 1: mixing lithium iron silicate particles, silicone oil A and an organic solvent to obtain a mixture a, wherein the silicone oil A is a polysiloxane containing at least two silicon-hydrogen bonds; Step 2: adding silicone oil B and a hydrosilylation catalyst to the mixture a of step 1 and mixing them to obtain a mixture b, wherein the silicone oil B is a polysiloxane containing at least two alkenyl groups; Step 3: spray drying the mixture b in step 2 to form lithium iron silicate particles with a surface coated with an organic silicon layer; Step 4: Mixing lithium iron phosphate particles, a carbon source, water, and lithium iron silicate particles coated with an organic silicon layer obtained in step 3, wherein the carbon source is an organic matter containing oxygen and / or nitrogen; and then forming secondary particles by spray granulation, wherein the secondary particles have a composite structure in which the lithium iron silicate coated with an organic silicon layer is a core and the lithium iron phosphate coated with the carbon source is a shell; Step 5: calcining the secondary particles obtained in step 4 under an inert atmosphere to obtain the composite material.
8. The method according to claim 7, wherein in step 1, the lithium iron silicate particles have a single crystal structure. 9 . The method according to claim 7 , wherein the particle size of the lithium iron silicate particles represented by D50 is 2 μm to 6 μm.
10. The method according to claim 7, wherein the silicone oil A is methyl hydrogen-containing silicone oil.
11. The method according to claim 7, wherein the organic solvent is selected from one or more of dichloromethane, chloroform, toluene, xylene and dichlorotoluene. 12 . The method according to claim 7 , wherein the ratio of the volume of the organic solvent to the mass of the lithium iron silicate is 0.5 L / kg to 5 L / kg. 13 . The method according to claim 7 , wherein the molar ratio of the lithium iron silicate particles to the silicone oil A is 1:0.01 to 1:0.
15. The method according to claim 7 , wherein the silicone oil B is vinyl silicone oil. 15 . The method according to claim 7 , wherein the molar ratio of the silicone oil A to the silicone oil B is 1:1 to 1:
4.
16. The method according to claim 7, wherein the hydrosilylation catalyst in step 2 is selected from one or more of Karstedt catalyst, chloroplatinic acid, chlororhodic acid, and chloroiridic acid.
17. The method according to claim 7, wherein the hydrosilylation catalyst in step 2 is a Karstedt catalyst.
18. The method according to claim 7, wherein the mass of the hydrosilylation catalyst is 0.001% to 0.05% of the total mass of the silicone oil A and the silicone oil B.
19. The method according to claim 7, wherein step 3 is performed using a spray dryer, wherein the drying temperature of the spray dryer is 50°C to 200°C.
20. The method according to claim 7, wherein the particle size of the particles obtained in step 3 represented by D50 is 2 μm to 6 μm.
21. The method according to claim 7, wherein in step 4, the lithium iron phosphate particles are of a single crystal structure. 22 . The method according to claim 7 , wherein the particle size of the lithium iron phosphate particles represented by D50 is 0.1 μm to 0.5 μm.
23. The method according to claim 7, wherein the carbon source in step 4 is selected from carbohydrates, polyethylene glycol, and polyacrylic acid.
24. The method according to claim 7, wherein the molar ratio of the lithium iron phosphate particles in step 4 to the lithium iron silicate in step 1 is 1:0.1 to 1:
1.
25. The method according to claim 7, wherein the molar ratio of lithium iron phosphate to carbon source in step 4 is 1:0.01 to 1:0.
1.
26. The method according to claim 7, wherein step 4 is performed using a spray dryer, wherein the drying temperature of the spray dryer is 50°C to 200°C.
27. The method according to claim 7, wherein the secondary particles obtained in step 4 have a particle size of 3 μm to 15 μm represented by D50.
28. The method according to claim 7, in step 5, the inert atmosphere is selected from nitrogen, argon, helium, and xenon.
29. The method according to claim 7, wherein the calcination temperature is 300°C to 800°C.
30. The method according to claim 7, wherein the calcination time is 2 h to 10 h.
31. The method according to any one of claims 7 to 30, wherein the composite material is the composite material according to claim 1.
32. A positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector; the positive electrode film layer comprises a composite material according to any one of claims 1-6, or comprises a composite material prepared by the method according to any one of claims 7-30. 33 . The positive electrode sheet according to claim 32 , wherein the positive electrode film layer further comprises a conductive agent and a binder.
34. A secondary battery, comprising the composite material according to any one of claims 1 to 6, the composite material prepared by the method according to any one of claims 7 to 30, or the positive electrode sheet according to claim 32 or 33.
35. A battery module, comprising the composite material according to any one of claims 1 to 6, the composite material prepared according to the method according to any one of claims 7 to 30, the positive electrode sheet according to claim 32 or 33, or the secondary battery according to claim 34.
36. A battery pack, comprising the composite material according to any one of claims 1-6, the composite material prepared according to the method according to any one of claims 7-30, the positive electrode sheet according to claim 32 or 33, the secondary battery according to claim 34, or the battery module according to claim 35.
37. An electrical device, comprising a composite material according to any one of claims 1 to 6, a composite material obtained according to the method according to any one of claims 7 to 30, a positive electrode sheet according to claim 32 or 33, a secondary battery according to claim 34, a battery module according to claim 35, or a battery pack according to claim 36.
Citation Information
Patent Citations
Composite particle for electrode and electrochemical device
CN101399336A
Anode active material, preparation method thereof and battery
CN103050694A